Release of adenosine from human neutrophils stimulated by platelet activating factor, leukotriene B4 and opsonized zymosan - S. Sipka; Z. Dinya; M. Koltai; P. Braquet; G. Szegedi (Hindawi Limited, 1992)
Isolated human polymorphonuclear leukocytes (PMNL) stimulated by platelet activating factor (PAF), leukotriene B4 (LTB4) or opsonized zymosan (OZ) released adenosine measured by thermospray high performance liquid chromatography mass spectrometry in the cell-free supernatants. Stimulation by PAF or LTB4 resulted in a bellshaped concentration-effect curve; 5 × 10−7 M PAF, 10−8 M LTB4 and 500 μg ml−1 OZ induced peak adenosine release, thus cytotoxic concentrations did not elevate adenosine level in the supernatants. Therefore adenosine release was characteristic of viable cells. As calculated from concentration-effect curves, the rank order of potency for adenosine release was PAF > LTB > OZ. These resuits suggest that adenosine, when bound specifically to membrane receptor sites, may initiate signal transduction, and, in co-operation with other inflammatory mediators, may modulate phagocyte function, e.g. production of chemoluminescence (CL).